2018
DOI: 10.3892/or.2018.6718
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑433 inhibits cell growth and induces apoptosis in human cervical cancer through PI3K/AKT signaling by targeting FAK

Abstract: The present study aimed to examine the role of microRNA-433 in the growth and death of cervical cancer cells. RNA isolation, reverse transcription-quantitative polymerase chain reaction analysis, an MTT assay, flow cytometry, and western blot analysis were used for this investigation. The results showed that the expression of microRNA-433 was downregulated in patients with cervical cancer. The disease-free survival and overall survival rates of patients with low expression levels of microRNA-433 were lower, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In particular, the mutations of PIK3CA E542K and E545K promote glycolysis and proliferation of CC in vitro and vivo [212]. NBPF1, ARHGAP17, miR-99b, -181a2/181b2, -338, -383, -433 and -489, as well as LncRNA ANRIL, CRNDE, NEAT1 and LINC01305 are involved in the proliferation, invasion, autophagy or EMT via PI3K/AKT pathway [213][214][215][216][217][218][219][220][221][222][223][224]. Currently, only preclinical trials of PI3K inhibitor LY294002 has revealed it significantly radiosensitized CC cell lines in vitro and vivo [225,226], and the terminated clinical trials of AKT inhibitor GSK2141795 (NCT01958112, Table 3) has tried to display a novel treatment approach to patients of CC.…”
Section: Nct02240212mentioning
confidence: 99%
“…In particular, the mutations of PIK3CA E542K and E545K promote glycolysis and proliferation of CC in vitro and vivo [212]. NBPF1, ARHGAP17, miR-99b, -181a2/181b2, -338, -383, -433 and -489, as well as LncRNA ANRIL, CRNDE, NEAT1 and LINC01305 are involved in the proliferation, invasion, autophagy or EMT via PI3K/AKT pathway [213][214][215][216][217][218][219][220][221][222][223][224]. Currently, only preclinical trials of PI3K inhibitor LY294002 has revealed it significantly radiosensitized CC cell lines in vitro and vivo [225,226], and the terminated clinical trials of AKT inhibitor GSK2141795 (NCT01958112, Table 3) has tried to display a novel treatment approach to patients of CC.…”
Section: Nct02240212mentioning
confidence: 99%
“…In the same way, microRNA-433 induced the HeLa apoptosis via PI3K/AKT signal [32]. PI3K/AKT is involved in regulation cisplatin-resistance in cervical cancer [33].…”
Section: Discussionmentioning
confidence: 75%
“…77,78 Focal adhesion kinase (encoded by PTK2) suppresses apoptosis but promotes growth, proliferation, survival, EMT, tumorigenesis, migration, and invasion of CC cells and its expression is positively correlated with the progression, metastasis, angiogenesis, and the poor prognosis and clinical outcomes of patients with CC. [79][80][81][82][83][84][85][86] The expression and activity of TNF-α (encoded by TNF) is associated with the apoptosis, chemosensitivity, DNA damage response, necrosis, proliferation, invasion, and EMT of CC cells, and its polymorphisms are further correlated with the risk of development, progression, and malignancy in patients with CC. [87][88][89][90][91][92][93][94][95][96][97][98][99][100] The genetic or epigenetic malfunction of p53 (encoded by TP53), a key tumor suppressor that coordinates the cell cycle process, proliferation, apoptosis, DNA damage repair, and metabolism, can drive CC pathogenesis; therefore, the restoration of its expression or functional activity has been suggested as a potential strategy for treating CC.…”
Section: Discussionmentioning
confidence: 99%
“…109,111 Moreover, the complex interactions between these hub targets via various genetic and signaling mechanisms may modulate diverse CC-associated pathologic cellular processes, confer the pharmacological effects of anti-CC therapies, and contribute to the development of therapeutic resistance. 60,85,[112][113][114][115][116][117][118][119][120][121] Figure 2. Protein-protein interaction network for cervical cancer-associated targets of FDY2004.…”
Section: Discussionmentioning
confidence: 99%